Increase Knowledge Mother about Giving Food Companion ASI (MP-ASI) Through Counseling Health - Eka Saudar Renaldi Sihombing (IJCS: International Journal of Community Service, 2022)
Training “Increasing Mother's Knowledge about Feeding endamping ASI (MP-ASI) through Counseling Health" could increase knowledge about Giving Food Companion ASI (MP-ASI). Enhancement knowledge and Skills for participant counseling health about Giving Food Companion ASI (MP-ASI) with method lecture. Empowerment of midwives and cadres in monitoring the provision of food Companion ASI (MP-AS I) expected could materialized with good with exists gift a number of example method gift food companion ASI.